The sociology of creativity: PART II: applications: the socio-cultural contexts and conditions of the production of novelty - Burns, T. R.; Corte, U.; Machado, N. (Human Systems Management, 2015)
This is Part II of a three-part article. The article is predicated on the principle that creativity is a universal activity, essential in an evolutionary perspective, to adaptation and sustainability. This manuscript on the sociology of creativity has three purposes: (1) to develop the argument that key factors in creative activity are socially based and developed; hence, sociology can contribute significantly to understanding and explaining human creativity; (2) to present a systems approach which enables us to link in a systematic and coherent way the disparate social factors and mechanisms that are involved in creative activity and to describe and explain creativity; (3) to illustrate sociological systems theory’s (Actor-Systems-Dynamics) conceptualization of multiple interrelated institutional, cultural, and interaction factors and mechanisms and their role in creativity and innovative developments in diverse empirical instances. The preceding segment of this article, Part I, introduced a general model of innovation and creative development stressing the socio-cultural and political embeddedness of agents, either as individuals or groups, in their creative activities and innovative productions. This second part, Part II, investigates the “context of innovation and discovery” considering applications and illustrations ranging from, for instance: (i) “the independent innovator or entrepreneur” who exercises creativity based on absorbing a field of knowledge, concepts, challenges, problems, solution strategies, creativity production functions or programs (and who is likely to be in contact with libraries, relevant journals and may be directly or indirectly in contact with a network of others); (ii) groups in their particular fields operating greenhouse types of organization driving problem-solving and creative activities – both self-organizing groups as well as groups established by external powers (whether a private company, a government, or a non-government organization or movement); (iii) entire societies undergoing transformations and radical development as in the industrial and later revolutions. Part III of this article investigates and analyzes “the context of receptivity, selection, and institutionalization” of novelty.